Burrow systems of Iranian jerboa (Allactaga Firouzi Womochel, 1978) - Mohammadi, Saeed; Kaboli, Mohammad; Karami, Mahmoud; Naderi, Gholamreza (Instituto de Ecología, A.C., 2010)
Iranian jerboa was recorded as a new species for Iran near village of Shah-Reza, Isfahan province. It is considered as a data deficient species according to IUCN criteria. Since, No data have been yet reported, on the relationship between architecture of burrows and the social organization of this species, this study aimed to identify the burrow systems of the species. We excavated 15 burrows of Iranian jerboa in the type locality of the species. The burrow system of Iranian jerboa is composed of three types including: temporary, summer and winter burrows. The length of tunnels were significantly different (P=0.00) in winter burrows. General burrow described for Small Five-toed jerboa Allactaga elater was similar with these burrows except having reproduction burrow. Results show that depth of nest chamber in third type of burrow was deeper than in temporary and summer (P=0.00, P=0.003 respectively).